2019
DOI: 10.3138/gsi.13.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the Past in Diasporic Spaces: Kurdish Reflections on Genocide Memorialization for Anfal

Abstract: Diasporas engage in a variety of practices and activities to commemorate past massacres and genocides that might have led to the formation of the diaspora in the first place. In this process, certain massacres can be constructed as the "chosen trauma" and consequently become a central element in commemoration practices and identity formation. In this paper, we discuss genocide memorialization in the context of the Iraqi Kurdish diaspora in Europe. We focus specifically on genocide memorialization of the Anfal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They concluded that the genocide is employed to legitimize KRG rule by pointing to collective trauma and shared victimhood. They found that Anfal, as the “chosen trauma”, has become an element of “nation-building mechanisms.” Building on this work, Baser and Toivanen’s “Remembering the past in diasporic spaces: Kurdish reflections on genocide memorialization for Anfal” (2019) considers how the memory of the Anfal and Halabja is reconstructed among the contemporary European Kurdish diaspora, a community formed partly because of the genocide itself. They argue that the articulations of distance within Anfal commemoration practices differ from the articulations that exist in the “homeland context and serve the special function of contributing to collective identity construction, and a sense of belonging, for the “exiled” and diaspora community.…”
Section: Background and Literature Review On The Kurdistan Genocidementioning
confidence: 99%
“…They concluded that the genocide is employed to legitimize KRG rule by pointing to collective trauma and shared victimhood. They found that Anfal, as the “chosen trauma”, has become an element of “nation-building mechanisms.” Building on this work, Baser and Toivanen’s “Remembering the past in diasporic spaces: Kurdish reflections on genocide memorialization for Anfal” (2019) considers how the memory of the Anfal and Halabja is reconstructed among the contemporary European Kurdish diaspora, a community formed partly because of the genocide itself. They argue that the articulations of distance within Anfal commemoration practices differ from the articulations that exist in the “homeland context and serve the special function of contributing to collective identity construction, and a sense of belonging, for the “exiled” and diaspora community.…”
Section: Background and Literature Review On The Kurdistan Genocidementioning
confidence: 99%
“…16 Nicole Watt's work examined the politics of commemoration in Halabja at the local level, 17 Mlodoch laid out the groundwork for a better understanding of victims' discourses and contested memory in post-genocide societies, 18 and Moradi demonstrated the politics of genocide commemoration and its impact on survivors of the Kurdish genocide. 19 Finally, Six-Hohenbalken 20 and Toivanen and Baser 21 looked at commemoration practices in the diaspora and how the legacy of the genocide is transmitted to the diaspora youth. As important as these works are, we believe that more articles that bring the survivors' and their descendants' voices to the fore are needed to better understand the long-term impact of genocidal events from almost four decades ago.…”
mentioning
confidence: 99%